Hasil Belajar Akuntansi Dalam Persepsi Cara Mengajar Guru Dan Minat Belajar Pada Siswa Kelas X SMK Batik 2 Surakarta Tahun Ajaran 2016/2017 - Fitriyani, Nisa, Drs. Sudarto, HS. MM (2017)
The purpose of this study was to determine: 1) the influence of teacher teaching method perception to the learning outcomes of accounting in X grade of SMK Batik 2 Surakarta academic year 2016/2017, 2) the impact of student's interest in learning towards the learning outcomes of accounting in X grade of SMK Batik 2 Surakarta academic year 2016/2017, 3) the influence of the way teacher teaching method perception and the learning interest towards learning outcomes of accounting in X grade of SMK Batik 2 Surakarta academic year 2016/2017. This type of research is quantitative associative. The population in this study are X grade students of SMK Batik 2 Surakarta with the number of 83 students. Samples were taken as many as 66 students with proportional random sampling technique by lottery. The data were obtained through a questionnaire and documentation that had previously been tested for validity and reliability. The data analysis technique used is multiple linear regression analysis, t test, F test, test R2, effective contribution and relative contribution. Based on the data analysis obtained by multiple linear regression equation, it shows as follows: Y = 52.213 + 0.342 X1 + 0.092 X2 This equation shows that the learning outcomes are influenced by how accounting teachers teach and interest in learning. Based on the analysis and discussion it can be concluded that: (1) teacher teaching method perception gives impact on learning outcomes of accounting students X grade of SMK Batik 2 Surakarta. This is proved by regression analysis which is obtain tcount > ttable is 2,777> 1,998 with significant value 0.007 < 0.05. (2) Interest in learning does not give effect on learning outcomes of accounting in X grade of SMK Batik 2 Surakarta. It is prooved by regression analysis which is obtain the value of tcount < t table namely 0.487 < 1.998 with 0.628 significance value > 0.05. (3) both of teacher teaching method perception and interest in learning gives impact on learning outcomes of accounting in X grade students of SMK Batik 2 Surakarta. It is proved by regression analysiswhich is obtain the value of fcount > f table namely 4.087 > 3.14 with a significance value of 0.021 < 0.05. (4) Variable of teacher teaching method perception gives the effective contribution amounted to 62.3%. Variable of interest in learning effectively contribute amounted to 13.3%, with a coefficient of determination (R2) of 0.756 or by 75.6%, while 24.4% is influenced by other variables not examined.